2018
DOI: 10.1016/j.jval.2017.09.004
|View full text |Cite
|
Sign up to set email alerts
|

EQ-5D-5L versus EQ-5D-3L: The Impact on Cost Effectiveness in the United Kingdom

Abstract: The 5L shifts mean utility scores up the utility scale toward full health and compresses them into a smaller range, compared with the 3L. Improvements in quality of life are valued less using the 5L than using the 3L. The 3L and the 5L can produce substantially different estimates of cost effectiveness. There is no simple proportional adjustment that can be made to reconcile these differences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
72
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 79 publications
(83 citation statements)
references
References 23 publications
9
72
2
Order By: Relevance
“…By contrast, the Devlin et al distribution was unlike the EQ-5D-3L distribution or mapped EQ-5D-5L distribution, displaying a large shift upwards in utility values combined with a narrowing of the overall distribution. We suggest that the Devlin et al distribution is a function of both a response shift and a change in the valuation system, and therefore is similar to the findings reported by Hernandez Alava et al [26] when exploring the impact of switching from the EQ-5D-3L to the EQ-5D-5L Devlin et al tariff on cost-effectiveness results. Overall, the distributional findings in this study validate those previously reported by Mulhern et al [25] on a smaller sample for England and those reported by Janssen et al [22] for EQ-5D-3L and EQ-5D-5L values across seven countries.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…By contrast, the Devlin et al distribution was unlike the EQ-5D-3L distribution or mapped EQ-5D-5L distribution, displaying a large shift upwards in utility values combined with a narrowing of the overall distribution. We suggest that the Devlin et al distribution is a function of both a response shift and a change in the valuation system, and therefore is similar to the findings reported by Hernandez Alava et al [26] when exploring the impact of switching from the EQ-5D-3L to the EQ-5D-5L Devlin et al tariff on cost-effectiveness results. Overall, the distributional findings in this study validate those previously reported by Mulhern et al [25] on a smaller sample for England and those reported by Janssen et al [22] for EQ-5D-3L and EQ-5D-5L values across seven countries.…”
Section: Discussionsupporting
confidence: 85%
“…Overall, the distributional findings in this study validate those previously reported by Mulhern et al [25] on a smaller sample for England and those reported by Janssen et al [22] for EQ-5D-3L and EQ-5D-5L values across seven countries. Given the recent NICE position statement recommending the use of the van Hout et al mapping algorithm for studies that have collected 5L data, we suggest the implications of our results for cost-effectiveness analysis conducted in the near future could be similar (but smaller in magnitude) to those outlined by Hernandez Alava et al [26]. Due to the upwards shift in utility values that we observed for the 5L respondents using the van Hout et al algorithm, primarily driven by a response shift, there is less utility space for potential gains to occur versus identical EQ-5D-3L respondents scored using the Dolan EQ-5D-3L tariff.…”
Section: Discussionsupporting
confidence: 53%
“…Both measures had good completion rates, however a noteable difference was that the DEMQOL scores tended to be higher, but cover a smaller range. This suggests that there is potential for different utility measures to give different results, as has been found previously [51] [52].…”
Section: Discussionsupporting
confidence: 57%
“…The 5L version appears to capture small changes in health-related quality of life. Nevertheless, according to Hernandez et al [31], in the UK the shift to the right, and the higher concentration of high utility values, could lead to lower QALY increments and higher incremental cost-effectiveness ratios (ICERs), except for treatments with high lifeyear gains, which may raise issues of historical consistency between past (with 3L) and future decisions. Continuing to use the crosswalk as an interim solution would not lead to major changes versus the 3L.…”
Section: Discussionmentioning
confidence: 99%